The special librarian in the Metropolitan Manila area a profile - Yabut, Astrida G. (Institute of Library Science, University of the Philippines Diliman, 1977)
This is a survey of one hundred eighty-nine librarians in one hundred twenty libraries in the Metropolitan Manila area. It is an attempt to arrive at a profile of the special librarians taking into account their personnel characteristics, qualifications, economic status and work experiences, services rendered, interest in professional growth or continuing education and professional activities. It also tries to compare special librarians with public and academic librarians based on materials available at the Institute of Library Science Library, University of the Philippines.